Natural rhythms of climate variability and anthropopressure (anthropopressure will not overcome the natural rhythms of climate variability) - Stankowski, Wojciech (Quaestiones Geographicae, 2025)
The transformations of the Earth’s atmosphere have always been conditioned by cosmic-astronomical factors and natural “life processes of the Earth.” Human pressure has been increasing for several thousand years, but only in the last three centuries has anthropopressure reached a global scale, modifying the state of the atmosphere. The rhythm of energy fluctuations over the last approximately 130,000 years, including the youngest millennia (the so-called Late Glacial and Holocene) and contemporary times with human influence, allow us to predict the approaching end of the current climatic optimum.